ANALISIS PENGARUH TINGKAT KEPADATAN TANAH TERHADAP NILAI CBR - Zalukhu, Pipen Deris Krisman; Siregar, Chandra Afriade (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
This research aims to analyze the influence of soil density levels on the California Bearing Ratio (CBR) value, which is one of the important parameters in road construction planning and design. This research was carried out using soil samples from several locations with varying levels of density. CBR testing was carried out in soil conditions with varying densities to evaluate the relationship between soil density and the resulting CBR values. The data obtained is analyzed using statistical methods to determine significant patterns or trends. The research results show that there is a positive correlation between the level of soil density and the CBR value, where an increase in soil density is associated with an increase in the CBR value. These findings provide important insights for road construction planning and soil quality assessment, and can be used as a reference in decision making regarding the selection and maintenance of soil materials for construction projects. The conclusion of this research is that increasing soil density can increase the CBR value, which in turn can increase the stability and bearing capacity of the soil in construction applications.